Analysis of The Distribution of Total Suspended Solids on The Coastal Sampang Coast Due To The Blega River Flow Using Satellite Image Data - Hendrata Wibisana; Primasari Cahya Wardhani; Masliyah (Future Science, 2022)
The total suspended solids in the river flow are the source of the sedimentation process, which will lead to the river mouth, namely the coast, which will experience this process on an ongoing basis. In this research, the case study investigated is the flow from the Blega River, which carries the total suspended solids to the coast of Sampang Regency, Madura, where the suspended solids will dissolve in the Sampang coastal waters to the Madura Strait. The purpose of this research is to find out and analyze whether the accumulation of suspended solids is more towards the east or west of the coast of Sampang so that later it can be done to forecast changes in the coastline of the coast. The method used in this research is to utilize remote sensing technology using satellite image data. The results obtained from the measurement of total suspended solids with Aqua MODIS satellite image data in March 2022 showed that more sediment was accumulated in the western part of the coast, so from this phenomenon, it can be predicted that the western coast approaching Bangkalan district will receive sedimentation contributions which will affect the coastline of Bangkalan district in the future. It can also be concluded that the reflectance data of satellite imagery can be used to create an algorithm for the distribution of total suspended solids in sloping coastal areas such as the coast of Sampang, Madura.